Policy based solutions of compatible software for building of cadastral database for unifying land administration in Vietnam - Khoa, Doan Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The 2013 Law on Land was promulgated and entered to power. The Law provides revised articles and new amendments of main contents in activities of surveys and evaluation of land resources to settle shortages the 2003 Land Law did not provide detail regulations for Ministry of Natural Resource and Environment (MONRE) had approved the project “Strengthening the land administration and land database” which will be implemented from 2017 to 2020. However, actually, Vietnam is using numerous software for land administration but they are not compatible among themselves. Therefore, the effectiveness of land administration works remains limited in many aspects. This paper provides a study of existing status of software technology policies for cadastral database and an analysis of existing shortages which have common reasons from incompatibility of these software. This paper, targeting the settlement of problems raising from practical activities, proposes policy solutions for building of compatible software to unify the land administration activities in Vietnam. Code: 16082001